Nat Turner and the rising in Southampton County - Allmendinger, David F. (Johns Hopkins University Press, 2014)
"In August 1831, in Southampton County, Virginia, Nat Turner led a bloody uprising that took the lives of some fifty-five white people--men, women, and children--shocking the South. Nearly as many black people, all told, perished in the rebellion and its aftermath. Nat Turner and the Rising in Southampton County presents important new evidence about the violence and the community in which it took place, shedding light on the insurgents and victims and reinterpreting the most important account of that event, The Confessions of Nat Turner. Drawing upon largely untapped sources, David F. Allmendinger Jr. reconstructs the lives of key individuals who were drawn into the uprising and shows how the history of certain white families and their slaves--reaching back into the eighteenth century--shaped the course of the rebellion."--Publisher's Web site